A Stromal Tumor Presenting as a Pseudoaneurysmal Dilation of the Small Bowel Mimicking a Lymphoma on FDG PET/CT. (January 2022) - Xiao, Liu; Wang, Yueqi; Li, Lin
Abstract : Abstract: An 84-year-old woman visited our hospital with hematochezia for 1 month. Abdominal CT and FDG PET/CT showed local thickening of the small intestine, resembling an intestinal aneurysmal dilatation. Thus, a lymphoma was suspected, and surgical resection was performed. The final pathology revealed an exophytic small bowel stromal tumor with perforation, causing pseudoaneurysmal dilation of the small bowel. This case emphasized the importance of considering a small bowel stromal tumor when faced with similar FDG PET/CT findings.